Behaviour and design of monotonically loaded reinforced concrete external beam-column joints. (June 2023) - Algassem, Omar; Vollum, Robert L.
Abstract: This paper describes an experimental investigation into the influence of beam reinforcement detailing, column axial load and shear reinforcement on the joint shear strength of reinforced concrete external beam-column connections. A series of twelve external beam-column joint specimens were tested in three groups of four specimens. Series 1 investigated the influence of beam reinforcement anchorage type and bend radius. Series 2 studied the influence of column axial load on joint shear strength while series 3 studied the influence of intermediate column bars and joint shear reinforcement. The paper presents the experimental results and describes the influence of the considered variables on joint shear strength. Three existing empirical design equations for external beam-column are evaluated using data from this program and previously tested beam-column joint specimens. Finally, design recommendations are made.